Sociodemographic disparities in purchases of fruit drinks with policy relevant front-of-package nutrition claims - Emily Duffy; Shu Wen Ng; Marissa G Hall; Maxime Bercholz; Natalia Rebolledo; Aviva Musicus; Lindsey Smith Taillie (Cambridge University Press, 2023)
Abstract Objective: Our objectives were to describe sociodemographic characteristics associated with the purchase of (1) any fruit drinks and (2) fruit drinks with specific front-of-package (FOP) nutrition claims. Design: Cross-sectional. Setting: USA Participants: We merged fruit drink purchasing data from 60 712 household-months from 5233 households with children 0-5 years participating in Nielsen Homescan in 2017 with nutrition claims data. We examined differences in predicted probabilities of purchasing any fruit drinks by race/ethnicity, income and education. We constructed inverse probability (IP) weights based on likelihood of purchasing any fruit drinks. We used IP-weighted multivariable logistic regression models to examine predicted probabilities of purchasing fruit drinks with specific FOP claims. Results: One-third of households with young children purchased any fruit drinks. Non-Hispanic (NH) Black (51·6 %), Hispanic (36·3 %), lower-income (39·3 %) and lower-educated households (40·9 %) were more likely to purchase any fruit drinks than NH White (31·3 %), higher-income (25·8 %) and higher-educated households (30·3 %) (all P < 0·001). In IP-weighted analyses, NH Black households were more likely to purchase fruit drinks with 'Natural' and fruit or fruit flavour claims (6·8 % and 3·7 %) than NH White households (4·5 % and 2·7 %) (both P < 0·01). Lower- and middle-income (15·0 % and 13·8 %) and lower- and middle-educated households (15·4 % and 14·5 %) were more likely to purchase fruit drinks with '100 % Vitamin C' claims than higher-income (10·8 %) and higher-educated households (12·9 %) (all P < 0·025). Conclusions: We found a higher likelihood of fruit drink purchases in lower-income, lower-educated, NH Black and Hispanic households. Experimental studies should determine if nutrition claims may be contributing to disparities in fruit drink consumption.